2017
DOI: 10.3389/fmicb.2017.01072
|View full text |Cite
|
Sign up to set email alerts
|

A Complex Endomembrane System in the Archaeon Ignicoccus hospitalis Tapped by Nanoarchaeum equitans

Abstract: Based on serial sectioning, focused ion beam scanning electron microscopy (FIB/SEM), and electron tomography, we depict in detail the highly unusual anatomy of the marine hyperthermophilic crenarchaeon, Ignicoccus hospitalis. Our data support a complex and dynamic endomembrane system consisting of cytoplasmic protrusions, and with secretory function. Moreover, we reveal that the cytoplasm of the putative archaeal ectoparasite Nanoarchaeum equitans can get in direct contact with this endomembrane system, comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 60 publications
6
57
0
Order By: Relevance
“…For instance, surface proteins homologous to hemolysine [8] could initiate such contacts as observed previously for acidophilic Micrarchaeota using cryo-electron tomography [5,17]. More recently, fusion of cell membranes of N. equitans and its host Ignicoccus hospitalis was observed by transmission electron microscopy [18].…”
Section: Introductionmentioning
confidence: 54%
“…For instance, surface proteins homologous to hemolysine [8] could initiate such contacts as observed previously for acidophilic Micrarchaeota using cryo-electron tomography [5,17]. More recently, fusion of cell membranes of N. equitans and its host Ignicoccus hospitalis was observed by transmission electron microscopy [18].…”
Section: Introductionmentioning
confidence: 54%
“…FS is generally performed in acetone containing up to several percent of OsO 4 and uranyl acetate (UA) aiming to stabilize sample structure and increase electron scattering. Recent studies on archaeal models indicated that OsO 4 can be excluded without loss of structure preservation and SEM contrast (Heimerl et al, 2017). The omission of OsO 4 also allows to preserve antigenicity after epoxy-embedding (Parthasarathy, 1995;Rachel et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies directed against the Ignicoccus A 1 ‐part of the ATP synthase (polyclonal anti‐A 1 antibodies were used in a dilution of 1:200), and antibodies directed against the acetyl‐CoA synthetase (ACS; polyclonal anti‐ACS antibodies were used in a dilution of 1:100) were raised in rabbits from the purified native complex (Heimerl et al, ; KĂźper, Meyer, MĂźller, Rachel, & Huber, ; Mayer et al, ). The monoclonal antibody against ß‐glucan chrysolaminarin was raised in mice and was purchased at Biosupplies (Australia).…”
Section: Methodsmentioning
confidence: 99%
“…For 3D reconstructions, we used serial ultrathin sections with a nominal thickness of 70 nm. Segmentation and 3D reconstruction of EM data was carried out with AMIRA (Thermo Fisher Scientific) as described previously (Heimerl et al, ).…”
Section: Methodsmentioning
confidence: 99%